Bakom kulisserna av konsumtion: En kvalitativ undersökning om produktplaceringar i tv-serien Emily in Paris och unga vuxnas varumärkesuppfattning. - Abrahamson,Hilla; Carlsson Ramirez,Camilo; Wiklund,Amanda (2024)
The aim of this thesis is to examine how young adults perceive product placements in the tv show Emily in Paris. The ambition is to achieve a greater understanding of how consumer purchase intention is influenced by product placements, as well as the impact of product placements on consumers' attitudes and awareness towards brands. To answer the research questions, a qualitative study has been conducted involving 12 semi-structured interviews along with a semiotic analysis. Episode one in season three of Emily in Paris was analyzed using thematic analysis. The study follows an abductive approach to explore and fulfill its purpose. The theoretical framework used consists of the Balance Model of Product Placement Effects, the Framework for Audience Response to Product Placements, and the Elaboration Likelihood Model. These theories contribute to a comprehensive understanding of the impact of product placement on consumers and are analyzed in conjunction with the collected data in a thematic analysis. The analysis displays diverse opinions on product placements from young adults, depending on factors such as familiarity, fit, integration level, and message. The study draws three conclusions. The first conclusion is that the fit and degree of integration of product placements in the narrative affect brand awareness. The second conclusion is that the purchase intention of young adults can be influenced by product placements after just one episode of a tv show. The final conclusion is that the consumer’s perception and attitude towards product-placed brands seem to be shaped by an unconscious process.
Keywords: Produktplacering; tv-serie; semiotik; marknadsföring; stealth marketing